Students' and teaching staff's perception of the adequacy of Airlangga University library services and facilities - Sumarsih, Endang (Institute of Library Science, University of the Philippines Diliman, 1991)
This study was conducted to find out users' perception on Airlangga University Library in terms of its services and facilities. It was designed to find out the strengths and the weaknesses of the library services and facilities and to determine the relationship of the perception and some factors such as experience, personal characteristics and subject disciplines. The descriptive survey method was used in the study. A questionnaire was devised and interviews were made. A stratified random sample of 350 was drawn from 1,163 students and teaching staff of Airlannga University who visited the library between December 27, 1990 to January 12, 1991.